Histological Evaluation of Retina after Photo Disruption for Vitreous Humor by Q-Switched Neodymium-Doped Yttrium Aluminium Garnet (Nd:YAG) Laser - Kameel Ghaly, Sally (J Lasers Med Sci, 2013)
Introduction: Rabbits’ eyes were exposed to vitreous humor liquefaction with Q - switched (sometimes called “ giant pulses”) Neodymium-Doped Yttrium Aluminium Garnet (Nd:YAG) laser using two different energy protocols (5 mJ X 100 pulse and 10 mJ X 50 pulse)with and without vitamin C administration. The histological changes in the retina were investigated to evaluate the protective role of vitamin C. Methods: The rabbits were divided into four main groups (n= 12 each). The first group was divided into three subgroups (n=4) and then treated with 5 mJ X 100 pulse (X means times) delivered to the anterior, middle and posterior vitreous humor respectively. The second group received a daily dose of 25 mg/Kg vitamin C for two weeks then was divided into three subgroups and treated with laser in the same manner as the first group.The third group was divided into three subgroups (n=4) and then treated with 10 mJ X 50 pulse delivered to the anterior, middle and posterior vitreous respectively. The fourth group received a daily dose of 25 mg/Kg vitamin C for two weeks then was divided into three subgroups and treated with laser in the same manner as the third group. After two weeks, rabbits were decapitated and histological examination for the retina was performed. Results: The results showed that, the anterior vitreous group exposed to 5mJX100 pulse and supplemented with vitamin C, showed no obvious change. Furthermore, all other treated groups showed alteration in retina’s tissues histology after laser. Conclusion: Application of Q-switched Nd: YAG laser in vitreous humor liquefaction induces changes in retina’s layers. Although there were some sorts of improvements in retinas supplemented with vitamin C, it cannot protect them against laser oxidative damage.